The Microscopic Structure of the Omentum in Healthy Dogs: The Mystery Unravelled. (23rd July 2015) - Huyghe, S.; de Rooster, H.; Doom, M.; Van den Broeck, W.
Summary: The canine omentum has many valuable properties but is still an underestimated organ. It contributes in many ways to the protection of the peritoneal cavity through its versatility on immunological level, but also through its role during angiogenesis, absorption, adhesion and fat storage. Despite a wide range of applications, the basic structure of the omentum is not well documented. This study provides an insight in the microscopic structure of the canine omentum through both light microscopic and electron microscopic investigations. Two regions could be distinguished in the canine omentum: translucent and adipose‐rich regions. The translucent regions were composed of two different layers: a continuous flattened mesothelium on top of a submesothelial connective tissue matrix. The adipose‐rich regions consisted of a substantial layer of adipocytes on which a flattened continuous mesothelium was present. Between those two layers, a few strands of collagen fibres could be detected. Large aggregates of immune cells, the so‐called milky spots, were not observed in the omentum of healthy dogs. Only a limited number of leucocytes, macrophages and neutrophils were found, scattered throughout the connective tissue in the translucent regions. At the level of the adipose‐rich regions, the immunological population was virtually non‐existent.